(untitled) (Olhar de Professor, 2025)
This article explores reading mediation and play as ways of promoting meaningful experiences between children and contemporary books aimed at children. As part of an ongoing master’s research project, the study combines the State of Knowledge with the case study method to investigate how reading mediation using picturebooks can create conditions for playful experiences. The research explores several elements, including reading, its mediations and mediators, children as active receivers, interactions between teachers and children, relationships between children-books-authors-illustrators, interactions between children themselves and play. The results indicate that mediation carried out by Early Childhood Education teachers with picturebooks is a fruitful action for mobilizing imagination, expression, play and establishing interactions among children, in addition to contributing positively to their reading development.